1990
DOI: 10.1590/s0006-87051990000200002
|View full text |Cite
|
Sign up to set email alerts
|

Propagação de pteridófitas in vitro e in vivo através de esporos

Abstract: Sujeitas ao processo de extinção, em decorrência do extrativismo, as samambaias arbóreas Dicksonia sellowana (Presl.) Hook e Cyathea schanschin Mart, das quais se obtémo xaxim, são espécies ainda pouco estudadas quanto à propagação. Com o objetivo de desenvolver um método adequado à propagação destas espécies, através de esporos, realizaram-se experimentos in vitro e in vivo. Para a desinfecção dos esporos, utilizaram-se soluções de hipoclorito de cálcio, em diferentes concentrações, ou de sódio, comparando-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
1
5
0
3
Order By: Relevance
“…It was obtained total decontamination and a high percentage of germination. On the other hand, Borelli et al (1990) obtained 50% contamination of D. sellowiana spores in 2% calcium hypochlorite solution. Raghavan (1989) reported that in general, liquid media were superior for fern spore germination and that it is likely that solid media prevents the breakage of spore coats.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was obtained total decontamination and a high percentage of germination. On the other hand, Borelli et al (1990) obtained 50% contamination of D. sellowiana spores in 2% calcium hypochlorite solution. Raghavan (1989) reported that in general, liquid media were superior for fern spore germination and that it is likely that solid media prevents the breakage of spore coats.…”
Section: Resultsmentioning
confidence: 96%
“…Nutrients as well as other factors are implicated in the growth and development of prothallus fern and in its sporophyte formation (Fernández et al 1996;1997). Borelli et al (1990) cultivated D. sellowiana spores in Jones and Knop (modified by Dyer) media and commented that the best results were obtained with decontamination carried out in a 2% sodium hypochlorite solution over a period of 10 or 20 minutes. Filippini et al (1999) observed the lowest percentages of spore germination of D. sellowiana under 43 and 2% of irradiance.…”
Section: Introductionmentioning
confidence: 99%
“…(Dicksoniaceae) é a única espécie dessa família, sendo que existem poucos dados sobre o crescimento do cáudice (Sehnem 1978) e fenologia da fronde (Hoehne 1930) dessa espécie na literatura. Por outro lado, Rogge et al (2000) estudaram a criopreservação, enquanto que Borelli et al (1990), Filippini et al (1999), Renner & Randi (2004) (Tryon & Tryon 1982). A espécie é uma das mais notáveis dentre as plantas que caracterizam as florestas do Brasil meridional, em especial as florestas com araucária, sendo conhecida popularmente por xaxim.…”
Section: Introductionunclassified
“…Esses substratos também foram os melhores na germinação dos esporos das samambaias arbóreas D. sellowiana, Cyathea schanschin e Alsophila sp. em comparação com terriço (Borelli et al, 1990). Acredita-se que a manutenção da umidade na superfície do substrato foi um fator importante para a germinação dos esporos e os substratos Plantmax HT®, espuma fenólica e vermiculita, aparentemente apresentaram a superfície mais seca.…”
Section: Resultados E Discussão Efeito De Substratos Em Casa-de-vegetunclassified